Size-groups of Choodai taken by different nets and in different localities - Sekharan, K V (Indian Journal of Fisheries, 2016)
At present, the boats fishing choodai do not normally venture out to more than 6-8 miles off the shore. Within this zone, there are separate fishing grounds for various types of nets which differ, among other things, in mesh size. But an analysis of the size-groups taken by them shows that the catches as a whole are supported mostly by the 0-year-class. This indicates that given the indices of abundance and the corresponding rate of growth of an year-class, it should be theoretically possible, from a study of mesh-selection, to determine in advance the period at which it (the year class) would enter the catches of a net; perhaps the approximate amount of total catches that could be expected during a particular season could also be estimated. The data collected should further be important from the point of view of evolving a proper exploitation policy. Investigation of selection has also to some extent become urgent in view of a controversy that has recently arisen in the fishery. The men who use shore-seines fish choodai within the coastal belt, 1-1.5 miles from the shore, and they feel that the operation of gill-nets both within and outside this range is detrimental to their trade. As there are indications that the use of gill-nets is hkely to increase rather than diminish in the coming years, this dispute is likely to become more serious in the future. Obviously, an important point to be clarified in this connection is whether both gill-nets and shore-seines operate on the same size-group or age-group at any time of the year.